Philippine medical thesaurus on anatomy musculoskeletal system and persons in Pangasinan - Capito, Jertrude B. (2004)
This study, a pioneer work in the making of the Philippine medical thesaurus in Pangasinan was undertaken primarily to collect, translate, and organize medical Pangasinan terms in the musculoskeletal system and persons in aid to the development of the first Medical thesaurus in Pangasinan language. At the start, the researcher had encountered a lot of obstacles and resistance from the Pangasinenses. The needed assistance for the project was met with negative reactions. The medical terms were highly technical and the unfamiliarity of the terms to them resulted in their reluctance to help which also the influence of the English language, intermixed with the native language and become the way of communication in all communities was a deterrent for the fast and easy collection of translated terms. To begin the research, the appropriate methodologies used in the research were carefully studied and weighted in terms of facility and usefulness. The initial step was downloading of the medical terms of the musculoskeletal system and the persons from the MeSH. The target was to translate these medical terms into Pangasinan terms. The ranked Pangasinan dictionaries were consulted first for any possible translations. If dictionaries could not provide enough translations, the researcher had gone to Pangasinan to look for native speakers. Prepared worksheets containing medical terms were provided to the respondents to give any translation of the given terms. A tape recorder and a diagram for the anatomy of the musculoskeletal system was used by the researcher as an instruments during the interviews.